Visitors’ Evaluation of Destination Attributes of Penglipuran Village - Suasapha, Anom Hery (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
Destinations attributes are important aspects of a tourist destination that will determine visitors' satisfaction. They are also essential for the DMO to understand the strengths and weaknesses of the destination, thus providing the DMO with important information to further develop the destination. Visitors' evaluation of the destination attributes of Penglipuran Village is still unknown. Therefore, his article aims to discuss the visitors’ evaluation of destination attributes of Penglipuran Village to understand attributes the visitors perceived as important and how they are performing. The research implemented a quantitative approach, using the survey as the main method to collect primary data concerning the perception of respondents toward the importance and performance of those destination’s attributes. The sample was determined purposively and chosen from a population of tourism students of Bali Tourism Polytechnic. Importance-Performance Analysis (IPA) was used to analyze the data collected from 157 respondents. The result shows that there are six attributes considered very important, with three out of those six performings impressively, while the other three are of poor performance. The result also indicates that eight attributes are considered not important, even though three of those are performing impressively, while the other five are performing poorly. Based on the result, this article recommended for the tourism management organization of Penglipuran Village to focus their attention and effort on attributes plotted on the fourth quadrant of the IPA, while providing suggestions to improve the performance of those important attributes deemed as having poor performance. Key words: evaluation; destination attribute; importance; performance; Penglipuran.